2014
DOI: 10.15225/pnn.2014.3.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Nurses on Prevention of Nosocomial Infections in post-stroke Patients

Abstract: Introduction. Nosocomial infections are associated with daily functioning of a hospital and constitute one of major medical issues. The role and duty of the nurse is to prevent hospital infections in every hospitalized patient, especially in post-stroke patients. Only nursing staff that is educated and aware of their actions is able to minimize the risk of infection and thus reduce the suffering of the patient.Aim. The purpose of the paper was to assess, quantitatively, nurses’ knowledge about nosocomial infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…According to a study conducted in Palestine, there is no significant difference in age-related knowledge and practices (P = 0.082 and 0.220, respectively) 3 . However, the findings of a study conducted in Poland that found a significant relationship between nurses' age and their knowledge of nosocomial infection (P = 0.001) are incompatible 24 . This could be ascribed to the disparity in education, culture, and ongoing training, as well as adherence to rules and laws, between developing country societies and European countries like Poland.…”
Section: Discussionmentioning
confidence: 96%
“…According to a study conducted in Palestine, there is no significant difference in age-related knowledge and practices (P = 0.082 and 0.220, respectively) 3 . However, the findings of a study conducted in Poland that found a significant relationship between nurses' age and their knowledge of nosocomial infection (P = 0.001) are incompatible 24 . This could be ascribed to the disparity in education, culture, and ongoing training, as well as adherence to rules and laws, between developing country societies and European countries like Poland.…”
Section: Discussionmentioning
confidence: 96%
“…Navedeni rezultat može biti posledica nedostupnosti epidemioloških podataka o broju prijavljenih bolesnika sa intrahospitalnom infekcijom, ali i nedovoljne svesti medicinskih sestara i tehničara o rizicima za nastanak i širenje bolničkih infekcija. Istraživanje sprovedeno u Poljskoj na odeljenjima neurologije je pokazalo da medicinske sestre mlađeg životnog doba, sa kraćim radnim stažom, pokazuju bolje poznavanje definicije i prevencije intrahospitalnih infekcija, te da se više pridržavaju mera prevencije i kontrole intrahsopitalnih infekcija u odnosu na medicinske sestre starijeg životnog doba, sa dužim radnim stažom [12].…”
Section: Diskusijaunclassified